Perceptive on Women Workforce Participation: - (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Market demand efficient and skilled person for any kind of job. That efficiency is lacking for women due to inadequate trainings and expertise hence they account to lesser numbers. Further, heterogeneous society in terms of religions, castes and ethnicity exhibits variations in education and work force participation among women. Though women constitute half of India’s population, their literacy rate and workforce participation is not in convergence with their numbers. Dissimilar job opportunities or lesser prevalence of job in the market, low wages for women as compared to men’s, for the same job done by both, in addition they are subject to sexual harassment are some of the causes for low female workforce participation.